1967
DOI: 10.1192/bjp.113.503.1101
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Chlorpromazine in Schizophrenia: A Ten Year Comparative Survey

Abstract: It is now just over a decade since chlorpromazine came into general use in psychiatry. Insulin coma treatment is no longer popular in the treatment of schizophrenia, yet no long-term comparative evaluation has been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…1982;Biehlet al 1986) and because of the increased morbidity and effect on outcome which may be attributable to the interaction. Markowe et al (1967) found the rate of suicide in schizophrenics to be almost fifty times that reported for the normal population. Markowe et al (1967) found the rate of suicide in schizophrenics to be almost fifty times that reported for the normal population.…”
Section: Depressive Disorder and Schizophreniamentioning
confidence: 86%
“…1982;Biehlet al 1986) and because of the increased morbidity and effect on outcome which may be attributable to the interaction. Markowe et al (1967) found the rate of suicide in schizophrenics to be almost fifty times that reported for the normal population. Markowe et al (1967) found the rate of suicide in schizophrenics to be almost fifty times that reported for the normal population.…”
Section: Depressive Disorder and Schizophreniamentioning
confidence: 86%
“…Schizophrenia in itself carries some risk of suicide (Fremming, 1951 ;Helgason, 1964;Markowe et al, 1967) and this risk will be greater if the patient is misdiagnosed as schizophrenia when in fact he is suffering from a depressive illness. Extra care should be taken, therefore, when administering a drug with a potential mood-depressant effect to a patient already at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest classes of antidepressant medications, which dominated the clinical landscape from the 1950s through the 1970s, were discovered serendipitously . Tricyclic antidepressants (TCAs) were developed in the 1950s in the wake of the discovery that chlorpromazine 16 , derived from early synthetic antihistamines, acted as an antipsychotic agent (Figure ). ,,− This breakthrough led to the synthesis and pharmacological evaluation of other analogues of 16 , such as imipramine 17 , the first TCA to be developed. Numerous efforts followed the development of 17 , including the introduction of amitriptyline 18 by Merck in 1961. For many years, TCAs were the standard of care for depression. , It was later discovered that TCAs exert their antidepressant affects by blocking both the serotonin transporter (SERT) and the norepinephrine transporter (NET), increasing extracellular concentrations of serotonin 19 and norepinephrine 20 , with little effect on dopamine (DA) 21 . , However, TCAs have promiscuous pharmacology, with agonist or antagonist activity at multiple muscarinic, adrenergic, histamine, serotonin, and NMDA receptor subtypes, which engender significant adverse effects (e.g., agitation, dry mouth, and seizure). ,, Moreover, TCAs are potent inhibitors of L-type calcium and sodium channels, leading to potentially lethal hypertension and arrhythmias . Thus, TCA overdose is often fatal, which limits the use of these compounds in a patient population which is at risk for suicidal behavior.…”
Section: History and Importance In Neurosciencementioning
confidence: 99%